2022
DOI: 10.1108/jsit-11-2020-0254
|View full text |Cite
|
Sign up to set email alerts
|

Factors of organizational adoption of enterprise architecture in Malaysian public sector: a multi group analysis

Abstract: Purpose The relevant importance of enterprise architecture (EA) to an organization has gained the attention of the public sector. However, its adoption rate remains slow on the uptake. Thus, this study aims to investigate the various factors associated with adoption intention based on the technological, organizational and environmental framework for federal and state types of public organizations to provide greater predictive accuracy and relevance of EA adoption in Malaysia’s public sector (MPS) context. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 104 publications
1
2
0
Order By: Relevance
“…The lack of significance of top management support contradicts previous studies on organizational m-commerce adoption (Otieno and Kahonge, 2014; Alfahl et al , 2017; Li and Wang, 2018). However, this finding aligns with studies by Intan Salwani et al (2009) and Ahmad et al (2022), which found that top management support is not significant in the adoption of e-commerce in SMEs in Pakistan and the adoption of enterprise architecture in the Malaysian public sector, respectively. This could be due to m-commerce adoption not being a priority for SMEs, who may be more focused on meeting the needs of their business partners (Intan Salwani et al , 2009).…”
Section: Discussionsupporting
confidence: 86%
“…The lack of significance of top management support contradicts previous studies on organizational m-commerce adoption (Otieno and Kahonge, 2014; Alfahl et al , 2017; Li and Wang, 2018). However, this finding aligns with studies by Intan Salwani et al (2009) and Ahmad et al (2022), which found that top management support is not significant in the adoption of e-commerce in SMEs in Pakistan and the adoption of enterprise architecture in the Malaysian public sector, respectively. This could be due to m-commerce adoption not being a priority for SMEs, who may be more focused on meeting the needs of their business partners (Intan Salwani et al , 2009).…”
Section: Discussionsupporting
confidence: 86%
“…On an ongoing basis, scientists from various branches of entrepreneurial activity seek and study the factors that affect the operation of enterprises at different stages of their life cycle, identifying the most important, influential factors among them. Clear examples are papers on relevant factors of enterprises by the following scientists: Kartanaite et al (2021) research essential factors for industrial enterprises; Ouyang et al (2022) determine factors in the construction industry using dynamic econometric analysis; Camilleri et al, (2022) review factors affecting family businesses in tourism and hospitality; Ahmad et al (2022) perform a multi-group analysis of essential factors of enterprise architecture; Shvindina et al (2022), Kravchenko et al (2022), Kazeem et al (2022) examine important factors for institutions in the medical field; Kaya (2022) analyze the factors of small and medium-sized enterprises using an adaptive model; and many others who study essential factors influencing the functioning of enterprises Maris (2022), Ozkan et al (2022), Seguer and Hasna (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…EA is a comprehensive and holistic tool for managing and maintaining alignment between business and IT [4] [8] [18][19] [20]. It assists companies in achieving their goals by designing information technology that supports the integration of business and IT strategies [18][21] [22][23] [24]. BITA is crucial management attention that supports managers in achieving organizational goals, improving workflow, increasing profitability, making informed IT investment decisions, maintaining competitive advantage, and enhancing organizational performance [18] [25].…”
Section: Introductionmentioning
confidence: 99%